The Varied Trajectories of Engaged Buddhism: New Works on Buddhist Environmental Ethics, Interdependence, and Racial Karma - Locke, Jessica (Journal of religious ethics, 2022)
This book discussion reads three works in contemporary Buddhist social ethics alongside one another: Ogyen Trinley Dorje’s Interconnected, David Loy’s Ecodharma, and Larry Ward’s America’s Racial Karma. Each of these works contributes to the subfield of engaged Buddhism, which aims to bring Buddhist value theory to contemporary social and political issues in order to effect social change. The rapid development of engaged Buddhism constitutes a particularly rich moment in the history of Buddhist thought, as Buddhist ethics is showing itself to be actively in process—a tradition in the midst of rapid transformation, revision, and cross-cultural application. This book discussion interrogates these three works with that metaphilosophical and historiographical issue in mind, analyzing the particular ways in which they contribute to challenging and reshaping the traditional contours of Buddhist ethics into a contemporary social and political register. In exemplifying the approaches of translation, extending, and applying, these works demonstrate the creative and experimental moment in which Buddhist social ethics finds itself today. Such adaptations of the Buddhist tradition are historiographically significant as innovations, while also of a piece with Buddhism’s history of intercultural transmission.